Long-term benefit of redo sympathetic renal denervation in a patient with resistant hypertension - Tokarek, Tomasz; Rajtar-Salwa, Renata; Rzeszutko, Łukasz; Bartuś, Stanisław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Sympathetic renal denervation (RDN) has been demonstrated as a potential treatment option for patients with resistant hypertension [1]. Despite discouraging results after the SYMPLICITY HTN-3 trial several techniques and catheters were introduced to the market and data confirming adequate and effective denervation are growing [1, 2]. In current guidelines invasive methods are not recommended as routine treatment of resistant hypertension [3, 4]. However, a highly selected group of patients not responding to aggressive medical treatment might benefit from this method [1–4].